TINJAUAN PERILAKU PIDANA KERAHASIAAN DATA KONSUMEN TERAKOMODIR DALAM IMPLEMENTASI FINANCIAL TEKNOLOGI BERDASARKAN UNDANG UNDANG NOMOR 4 TAHUN 2023 - PRIATMOKO, ARI (Jurnal HUKUM BISNIS, 2026)
Accelerating the development of financial technology is mandated by law. A crucial aspect of financial technology management is its relationship to managing customer data confidentiality. Misuse of customer data remains rampant. Therefore, the purpose of this research is to determine that customer data confidentiality constitutes a criminal offense, requiring managers to exercise extreme caution. This research utilizes a normative juridical legal method with a statutory regulatory and conceptual approach. Therefore, the writing relies on primary sources, namely laws and expert opinions/doctrines. The results of the research indicate that data confidentiality is an essential principle in digital business activities, particularly in digital banking, and serves as an instrument for protecting data subjects' privacy rights. Financial institutions have a legal obligation to maintain the security and confidentiality of the personal data they manage. Keywords: Fintech, Customer Confidentiality, Object of Criminal Offense, Tipidter